Rethinking the MBA : business education at a crossroads - Datar, Srikant M.; Garvin, David A.; Cullen, Patrick G. (Patrick Gerard) (Boston, Mass. : Harvard Business Press, 2010)
This book provides case studies showing how leading MBA programs have begun reinventing themselves for the better. Also offer concrete ideas for how business schools can surmount the challenges that come with reinvention, including securing faculty with new skills and experimenting with new pedagogies. Rich with examples and thoroughly researched, this book also helps to reveals why and how business schools must define a better pathway for the future.
Introduction : a degree in transition -- The changing MBA marketplace -- A close look at the curriculum -- A rising chorus of concerns -- Meeting the challenges of globalization, leadership, and integration -- Innovations in pedagogy and course design -- University of Chicago Booth School of Business : flexibility and the discipline-based approach -- INSEAD : the credo of globalization -- The Center for Creative Leadership : leadership development at the core -- Harvard Business School : general management and the focus on practice -- Yale School of Management : integration and large-scale change -- Stanford Graduate School of Business : customization and large-scale change -- Conclusion : business schools at a crossroads.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Business education -- United States; Master of business administration degree -- United States; Business schools -- United States; Business education; Business schools; Master of business administration degree; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Reference; BUSINESS & ECONOMICS / Skills; United States; elektronické knihy; electronic books